Studies on the Quality and Health Status of T. Aman Rice Seeds Collected From Different Sources (Research in Agriculture Livestock and Fisheries, 2022)
A laboratory experiment was carried out at the Professor GAF Seed Pathology Centre and Laboratory of Department of Seed Science and Technology, Bangladesh Agricultural University (BAU), Mymensingh during the period of July 2018 to January 2019 to determine the effect of seed sources on quality and health status in some Transplanted Aman rice varieties in Bangladesh. Among the seed sources, the moisture content was recorded from 10.40% to 13.37%. In case of purity analysis of seed pure seed ranged from 39.23g to 39.94g. Germination test of rice seeds was recorded and the percentage of total number of germination ranged from 55.75% to 93.0%, normal seedling (51.50 % to 86.50%), abnormal seedling (4.75 % to 10.75%), fresh ingeminated seed (1.75% to15.0%), hard seed (0.0 % to 11.75%), dead seed (2.75% to 21.25%), respectively. Vigour index in the seed sources ranged from (1255.80 to 2089.86). In dry inspection test apparently healthy seeds (17.74gto 28.92g), spotted seeds (9.8g to 17.34g), deformed seeds (0.36g to 5.58g), discolored seeds (0.34g to 3.40g), inert mater (0.00g to 0.38g), insect damaged seeds (0.00g to 0.24g) and chaffy seeds (0.08 g to 1.14g) were recorded(2.75% to 21.25%), respectively. In the seed health study, seven species of fungi were recorded. In the seed health test Alternaria padwickii (1.25 % to 5.50%), Aspergilus niger (0.0% to 1.75%), Bipolaris oryzae (0.0% to 1.50%), Curvularia lunata (0.00% to 1.0%), Aspergillus flavus (0.00% to 1.25%), Penicillium sp. (0.00% to 1.50%) were recorded, respectively. Most of the farmers were failed to obtain the quality and good health status. In this study, BRRI dhan34 in farmer's seed recorded the highest performance in the seed sources and the lowest performance was recorded in BRRI dhan49 in farmer's seed. Among the seed sources BR22 of BADC seed (T8) performed the best in respect of seed quality and seed health.Vol. 9, No. 2, August 2022: 103-116